The Potential of Microgreens in Indonesian Traditional Food Innovation: Opportunities, Challenges, and Culinary Innovation Based on Literature Studies - Dewi, Margriet Puspa (Journal of Management and Administration Provision, 2024)
Microgreens are young plants that are harvested in the early stages of growth, generally still in the form of sprouts that are 7-21 days old. In addition to containing high and adequate nutrients, microgreens also contain biotic compounds that are able to increase the body's metabolism. In recent years, the use of microgreens in the culinary world has continued to increase, including in Asia and Indonesia. This study aims to examine the use of microgreens as an additive to Indonesian typical foods by reviewing national and international scientific literature during the period 2020–2025. The method used was a documentation study with a thematic analysis approach to 20 relevant journals. The results of the study show that microgreens have the potential to be an innovative ingredient in the presentation of traditional and modern foods in Indonesia, especially in an effort to improve nutrition, aesthetic value, and market acceptance of healthy foods. A number of challenges such as short shelf life, production costs, and understanding the benefits of microgreens still need to be addressed. The study recommends the integration of microgreens in locally-based culinary innovations as a strategic opportunity in the development of healthy and sustainable food.